Effects of a nurse-coordinated prevention programme on health-related quality of life and depression in patients with an acute coronary syndrome: results from the RESPONSE randomised controlled trial. Issue 1 (December 2016) - Jørstad, Harald; Minneboo, Madelon; Helmes, Harold; Fagel, Nick; Scholte op Reimer, Wilma; Tijssen, Jan; Peters, Ron
Abstract Background Improvement of health-related quality of life (HRQOL) is an important goal in preventive cardiology. HRQOL is also related to depressive symptoms, which represent a common co-morbidity and risk factor in patients with an acute coronary syndrome (ACS). Comprehensive nurse-coordinated prevention programmes (NCPP) in secondary care have been shown to reduce cardiovascular risk, however their effects on HRQOL and depressive symptoms have not been evaluated. We therefore investigated HRQOL and depressive symptoms in a secondary analysis in the RESPONSE trial, evaluating the effect of a NCPP on cardiovascular risk. Methods RESPONSE was a multicentre (n  = 11) randomised controlled trial in ACS-patients in secondary and tertiary healthcare settings evaluating a NCPP. The intervention consisted of four outpatient nurse clinic visits in the first 6 months after the index event, focusing on healthy lifestyles, biometric risk factors and medication adherence, in addition to usual care. The control group received usual care only. The outcome was change in HRQOL as measured by the MacNew questionnaire and change in depressive symptoms as measured by Beck's Depression Inventory (BDI) questionnaire at 12-months follow-up relative to baseline. Results Of 754 patients randomised, 615 were analysed for HRQOL; 120 for depressive symptoms. At baseline, HRQOL was 5.17 (SD 1.09) and 5.20 (SD1.04) (scale range 1.0 to 7.0) in the intervention and control group, respectively. At 12 months follow-up, HRQOL increased by 0.57 (SD 0.89) in the intervention group as compared with 0.42 (SD 0.90) in the control group (p  = 0.03). This increase was observed across all relevant subscales. The BDI decreased by 1.9 in the intervention group as compared with 0.03 in the control group (p  = 0.03) (scale range 1.0 to 63). Conclusion Participation in a NCPP is associated with a modest but statistically significant increase in HRQOL, and a decrease of depressive symptoms, both of which are highly relevant to patients. A reduction in depressive symptoms may in addition contribute to a reduction in the overall risk of recurrent events. Trial registration Dutch trials register:NTR1290 . Registered 24 April 2008.